ANALISIS YURIDIS TERHADAP PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DAN PENGARUHNYA TERHADAP PENERIMAAN PAJAK DAERAH DI KOTA MEDAN - Elya Deswita (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Implementation of land registration throughout the territory of the Republic of Indonesia is the obligation of the government and right holders in accordance with the Basic Agrarian Law, Law Number 24 of 1992 and most recently Minister of Agrarian Regulation number 6 of 2018. Land registration is a requirement to achieve legal certainty guarantees and legal protection of land rights. In addition to registering land functions to protect the owner, it also functions to find out the status of a parcel of land, who is the owner, what are the rights, how wide, for what is used and so on. Guarantees of legal certainty to be realized in the registration of this land include certainty of the status of the rights registered, certainty of the subject of rights and certainty of the object of rights. This registration produces a certificate as proof of the rights of the land owner.